Improving Access for Pediatric and Adult Cochlear Implant Candidates in Ontario - Yvonne Emily James (Health Reform Observer - Observatoire des Réformes de Santé, 2016)
In 2011, the Ontario Ministry of Health and Long-Term Care announced the one-time allocation of $5.9 million to be shared by cochlear implant programs at five Ontario hospitals. The primary goal of this reform was to address cochlear implant wait times. More specifically, this funding was aimed at reducing adult wait times by 50% and to completely eliminate pediatric waiting lists. Prior to this funding, wait times for pediatric and adult cochlear implants were known to exceed four years. The funding was provided in response to a growing body of research that demonstrates increased speech perception and vocabulary among pediatric recipients, and pressure from parents of children on cochlear implant waiting lists, surgeons and other involved healthcare providers (e.g., auditory verbal therapists, audiologists, and speech language pathologists). The decision to increase funding was also influenced by government stakeholders who believed this one-time investment would be returned as pediatric patients reach adulthood and are better equipped to participate in mainstream (i.e., hearing) society. While this one-time funding model has the potential to eliminate wait times for pediatric patients, thereby ensuring these children can access therapeutic services as early as possible, it does not address the future of cochlear implant waiting lists or the capacity of health human resources to absorb this sudden and unprecedented influx of pediatric patients.